Computed tomography and magnetic resonance imaging findings in dogs with vaginal leiomyoma and leiomyosarcoma. Issue 6 (5th September 2022) - Tanaka, Toshiyuki; Noguchi, Shunsuke; Wada, Yusuke; Yamazaki, Hiroki; Nishida, Hidetaka; Akiyoshi, Hideo
Abstract: Background: In humans, magnetic resonance imaging (MRI) is preferred over computed tomography (CT) for the assessment of pelvic lesions. Although CT findings of several pelvic tumours have been reported in veterinary medicine, MRI findings are limited. Objectives: The purpose of this study was to retrospectively compare the CT and MRI findings in dogs with vaginal leiomyoma and leiomyosarcoma. Methods: This retrospective study of five dogs compared the CT and MRI findings of intrapelvic lesions, including vaginal leiomyoma ( n  = 4) and leiomyosarcoma ( n  = 1). No invasion of the surrounding tissue was detected on histopathological examination. In this retrospective study, the following parameters of CT and MRI were recorded for each dog: the border between the lesion and the adjacent pelvic organs, including the prostate, rectum or urethra; signal intensity (SI) of the lesion; enhancement pattern; presence of haemorrhage; necrosis or cystic areas and lymphadenopathy. Because SI on MRI is affected by cell density, tumour cell density was analysed using a microscope slide. Results: In vaginal leiomyoma, the border between the lesion and the surrounding pelvic organ tends to be clearer on MRI than on CT. In vaginal leiomyosarcoma, the border was comparable between MRI and CT. Each lesion showed heterogeneous enhancement on CT and MRI scans. In each lesion, the assessment of haemorrhage, necrosis, cystic areas and lymphadenopathy was comparable between MRI and CT. The SI of the lesion on T2WI of the vaginal leiomyoma and leiomyosarcoma were hyperintense in four cases (4/4; 100%) and mixed intense in one case (1/1; 100%), respectively. The cell density of leiomyosarcoma is higher than that of leiomyomas. Conclusions: The SI on T2WI may be useful for differentiating leiomyoma from leiomyosarcoma. MRI may be useful to differentiate vaginal leiomyomas from leiomyosarcomas and evaluate margins. Abstract : This study compared the CT and MRI findings in dogs with pelvic lesions, including vaginal leiomyoma and vaginal leiomyosarcoma. MRI was superior to CT in assessing clear boundary between the pelvic lesions and adjacent organs. In addition, MRI may be useful for differentiating vaginal leiomyoma from leiomyosarcoma.